Simulation Studies Of Push, Conwip And Modified Conwip Systems In A Wafer Fabrication Environment - Muhammad, Nur Amalina (2014)
Wafer fabrication is a front-end semiconductor manufacturing. Notoriously complex, it has attracted voluminous researchers to improve its production planning and control. This study is a fundamental research with the aim to obtain greater understanding of the basic aspects of conwip-based systems in the wafer fabrication environment. This comparison was achieved by five production control systems in a manufacturing environment emulating the complexity of wafer fabrication. These include push, constant work-in-process (conwip) and modified conwip systems (conload, m-conwip and nested conwip). Except nested conwip, the other systems are methods established in different industries. Nested conwip is a newly conceived method in this research to allow early release of complementary cards to influence job selection. Characteristics of interest relevant to wafer fabrication are the re-entrant process flow, job dependent setup, job mix, priority and batching. The performance measures considered are total output (to), total critical output (tco), average flow time (avgft), standard deviation flow time (sdft), average waiting time (avgwt) and machine utilization (mutil). The study was performed by using the discrete event simulation and statistical analysis. The selection of parameters, variables and performance measures in the simulation was relatively based on a wafer fabrication case study. For statistical analysis, analysis of variance (anova) determined the relationship between variables and performance measures for each system.